Eu(s): corpo negro e o poder das imagens na autorrepresentação de mulheres negras - Mayara Smith Xavier (2024)
The aim of this research is to discuss the power of images in the creation of stereotypes and representation of black women in the field of visual arts. With the help of self-representation, black women artists from the past and contemporary artists create images that challenge the racist , patriarchal, and sexist narratives typically associated with black bodies. They demonstrate their subjectivity, sensitivity, beauty, and ancestry through images that break away from colonial memory and seek to rectify the erasure of the past. To accomplish this, I draw upon various works by black artists and intellectuals who speak from a decolonial perspective on how to rethink art spaces in academic and curatorial circles, fostering an attentive gaze towards the Other. I conduct an analysis of my own authorial production on the relationship as a black woman with self-portraiture, exploring the themes of identity and connection with subjectivities and ancestry. Additionally, the text incorporates the experiences of other black women artists with self-representation and the empowering nature of this act as resistance.